ANALISIS PENCATATAN DAN PELAPORAN KEUANGAN PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI SULAWESI UTARA - Kumaat, Anggi Kartika; Morasa, Jenny; Kalalo, Meily Y. B. (Universitas Sam Ratulangi, 2015)
Financial recording and reporting are very important in a company. SKPD is works unit of the region government in the capacity of budged user/commodity user. Each and every region work unit provide information about financial recording and reporting. In this study the object taken at Department of Marine and Fishery of North Sulawesi Province.Â This study aims to show how financial recording and reporting appropriate with government regulation number 71 yaerÂ 2010 cornerning governmental accounting standard ang internal affairs minister regulation number 57 year 2007 concerning regional financial management and to identify constraint which is faced by department of marine and fishery of north Sulawesi province. The research method used is qualitative method by collecting financial report, general overview of the company, and analyze financial recording and reporting. The results showed that the financial recording and reporting the Department of Marine and Fishery of North Sulawesi Province is not in accordance with the regulation No. 71 year 2010 concerning Governmental Accounting Standards for the presentation are not included Cash Flow Statement, Statement of Changes Equity, Statement of Changes in Balance Budget Surplus, and operational reports.